Analysis of the Quantitative Evaluation of the Public Medical and Health System Costs During Pandemic Governance: Investigation Based on COVID-19 - Li, Xintao; Zhang, Zaisheng; Liu, Li; Cheng, Tongshun; Liu, Gang (Frontiers in Public Health, 2022)
It is of great reference significance for broadening the research perspective of pandemic governance, improving the efficiency of pandemic governance and the credibility of the government, to scientifically measure and analyze the public medical and health system costs. This article takes the typical case “pandemic prevention and control event of S city, China” as the research background. First, the concept of public medical and health system costs during pandemic governance is defined. Then, the public medical and health system costs are embedded into the pandemic governance system, and the generation process of the public medical and health system costs in the actual situation are investigated. Furthermore, through in-depth interview, multi-case grounded theory and fuzzy subordinate function analysis, the scientific construction of the public medical and health system cost index system are completed. Finally, based on G1 method/entropy method combined with weighting and fuzzy comprehensive evaluation method, the public medical and health system costs of the pandemic prevention and control events of S city is measured. The results show the following: (1) it is important that good single dimensions and reliable indicators are embodied in the public medical and health system costs scale. Among them, the behavioral public medical and health system costs of the masses is the largest proportion of all indicators; (2) after the pandemic prevention and control event is over, the public medical and health system cost are difficult to repair, and some lagging ideas and behaviors shown by local governments lead to a continuous expansion of the public medical and health system costs associated with pandemic governance; and (3) local governments should not conceal information asymmetry. Instead, local governments should give greater freedom to other actors to deal with pandemic governance, and governance entities should cooperate with each other. This will mitigate the effect of public medical and health system costs. Corresponding policy recommendations are proposed.